2014
DOI: 10.3758/s13415-014-0290-y
|View full text |Cite
|
Sign up to set email alerts
|

Intersubject variability in fearful face processing: the linkbetween behavior and neural activation

Abstract: Stimuli that signal threat show considerable variability in the extent to which they enhance behavior, even among healthy individuals. However, the neural underpinning of this behavioral variability is not well understood. By manipulating expectation of threat in an fMRI study of fearful vs. neutral face categorization, we uncovered a network of areas underlying variability in threat processing in healthy adults. We explicitly altered expectation by presenting face images at three different expectation levels:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 68 publications
1
16
0
1
Order By: Relevance
“…That rhythmic breathing paces electrical activity in the human brain to modulate behavior raises the intriguing possibility that other physiological and autonomic rhythms, and even periodic sampling in other sensory domains (Kepecs et al, 2006;Moore et al, 2013;Ito et al, 2014), might also shape neuronal oscillations to optimize human perception, emotion, and cognition. We would note that, while the effect sizes of our behavioral results are relatively modest (e.g., a 28 ms difference between fear inhalation and fear exhalation for the nasal route; a 60 ms difference between fear inhalation/exhalation for the nasal vs oral route), the magnitude of the changes is on par with those found in many other cognitive studies examining the effects of facial emotion on perceptual discrimination, with differences typically in the range of 20 -100 ms (Doty et al, 2014;Li et al, 2014;Ye et al, 2014).…”
Section: Discussionmentioning
confidence: 60%
“…That rhythmic breathing paces electrical activity in the human brain to modulate behavior raises the intriguing possibility that other physiological and autonomic rhythms, and even periodic sampling in other sensory domains (Kepecs et al, 2006;Moore et al, 2013;Ito et al, 2014), might also shape neuronal oscillations to optimize human perception, emotion, and cognition. We would note that, while the effect sizes of our behavioral results are relatively modest (e.g., a 28 ms difference between fear inhalation and fear exhalation for the nasal route; a 60 ms difference between fear inhalation/exhalation for the nasal vs oral route), the magnitude of the changes is on par with those found in many other cognitive studies examining the effects of facial emotion on perceptual discrimination, with differences typically in the range of 20 -100 ms (Doty et al, 2014;Li et al, 2014;Ye et al, 2014).…”
Section: Discussionmentioning
confidence: 60%
“…In the field of social face perception, researchers tend to use specific sets of standardized stimuli (e.g., Beaupré et al 2000, Langner et al 2010, Lundqvist et al 1998, Matsumoto & Ekman 1988 to probe different social perceptions and their associated brain activities (Doty et al 2014). However, classic use of these stimuli cannot identify the information ontology of a social perceptioni.e., what stimulus information is driving behavior (or brain activity).…”
Section: Exposing Face Information To Identify Diagnostic Informationmentioning
confidence: 99%
“…We investigated the functional connectivity of the vmPFC, rAMY and rTPJ, with strong evidence for involvement of these brain regions in emotion perception influenced by prior expectations (Barbalat et al, 2013;Doty et al, 2014;Dzafic et al, 2016). In line with our hypotheses, our findings show that facilitation of response to threat congruent with prior expectations was associated with a subcortical network functionally connected to rAMY.…”
Section: Discussionsupporting
confidence: 69%
“…Functional networks were mapped for the three seed regions identified in Chapter1, the vmPFC, rAMY and rTPJ . Previous literature has implicated these regions in threat processing (Doty et al, 2014;Marstaller et al, 2016) and rapid re-orienting of attention to relevant stimuli (Corbetta et al, 2008). I found that faster recognition of congruent threat was associated with a subcortical network functionally connected to rAMY, implicated in fear conditioning and rapid processing of coarse emotional cues.…”
Section: Contributions To the Literaturementioning
confidence: 80%
See 1 more Smart Citation